Perbandingan Metode Algoritma C4.5 Dan Naïve Bayes Untuk Menganalisa Review Pengguna Layanan Ekspedisi JNE Melalui Aplikasi Google Playstore - Oktalia, Cici; Zakaria, Hadi (CV. Shofanah Media Berkah, 2024)
E-commerce, is a platform for selling products and services online and is heavily dependent on the logistics industry, especially shipping services. The large number of online sales transactions has increased the number of users of shipping services. One of the companies operating in the field of shipping services in Indonesia is Tiki Jalur Nugraha Ekakurir or better known as JNE. The existence of this JNE expedition service allows e-commerce to divert their attention from the aspects of inventory to a more centralized distribution of products. JNE's been up and down in his performance. Based on Google Play, My JNE has the lowest rating. Some of the complaints that customers submit on Google Play are most often submitted are package delays, pricing inconsistencies, packages received in damaged condition, and more. The study analyzed customer reviews related to JNE expedition services available on the Google Play platform using the C4.5 algorithm method and the Naïve Bayes Algorithm to determine the speed and accuracy of calculations using which method is more efficient and accurate. Overall, this research provides insight into how classification methods can be used to analyze customer reviews and understand sentimental expedition services.